2018
DOI: 10.1101/399659
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling motor neuron resilience in ALS using stem cells

Abstract: Running title: Modeling motor neuron resilience in ALS SUMMARYOculomotor neurons, which regulate eye movement, are resilient to degeneration in the lethal motor neuron disease amyotrophic lateral sclerosis (ALS). It would be highly advantageous if motor neuron resilience could be modeled in vitro. Towards this goal, we generated a high proportion of oculomotor neurons from mouse embryonic stem cells through temporal overexpression of Phox2a in neuronal progenitors. We demonstrate, using electrophysiology, immu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…We analyzed mRNA expression of four independent D2KO motor neuron cultures, four D10KO (clone G4) motor neuron cultures and eight independent cultures of the parental control motor neurons. Comparison of our parental motor neuron RNA sequencing dataset by principal component analysis (PCA) to available human iPSC-motor neuron datasets (GSE108094 (Rizzo et al, 2019), GSE121069 (Nijssen et al, 2018)) and laser captured post mortem human motor neuron datasets (GSE76220 (Batra et al, 2016), GSE76514 (Nichterwitz et al, 2016), GSE93939 (Allodi et al, 2019)) showed tight clustering of our 8 samples together, supporting consistent, high-quality differentiation conditions of our cultures ( Figure 4A). Interestingly, PCA of all of our samples alone showed that the expression profiles of D2KO and D10KO motor neurons complete overlapped and were separate from parental control motor neurons ( Figure 4B).…”
Section: Chchd10 and Chchd2 Knockout Motor Neurons Have Overlapping Tsupporting
confidence: 70%
See 1 more Smart Citation
“…We analyzed mRNA expression of four independent D2KO motor neuron cultures, four D10KO (clone G4) motor neuron cultures and eight independent cultures of the parental control motor neurons. Comparison of our parental motor neuron RNA sequencing dataset by principal component analysis (PCA) to available human iPSC-motor neuron datasets (GSE108094 (Rizzo et al, 2019), GSE121069 (Nijssen et al, 2018)) and laser captured post mortem human motor neuron datasets (GSE76220 (Batra et al, 2016), GSE76514 (Nichterwitz et al, 2016), GSE93939 (Allodi et al, 2019)) showed tight clustering of our 8 samples together, supporting consistent, high-quality differentiation conditions of our cultures ( Figure 4A). Interestingly, PCA of all of our samples alone showed that the expression profiles of D2KO and D10KO motor neurons complete overlapped and were separate from parental control motor neurons ( Figure 4B).…”
Section: Chchd10 and Chchd2 Knockout Motor Neurons Have Overlapping Tsupporting
confidence: 70%
“…RNA-seq data from the motor neurons in this study were contrasted to publicly available datasets of other human iPSC derived motor neurons; GSE108094 (Rizzo et al, 2019) and GSE121069 (Nijssen et al, 2018) as well as laser captured motor neurons; GSE76220 (Batra et al, 2016), GSE76514 (Nichterwitz et al, 2016) and GSE93939 (Allodi et al, 2019). The same analysis procedures (trimming, mapping and read counting) were applied to the reference samples as for our dataset.…”
Section: Rna Sequencingmentioning
confidence: 99%
“…RNA-Seq human data mining was performed using data from NCBI GEO/SRA repositories: spinal motor neurons (GEO GSE93939) 71 ; prefrontal cortex (GEO GSE102556) 72 ; cerebellum (GEO GSE97942) 73 ; DRG (SRA SRP077657), iPSCs (GEO GSE120081); iPSC-derived sensory neurons (GEO GSE26867) 35 ; fibroblast-derived nociceptors (SRA SRP165240) 38 .…”
Section: Methodsmentioning
confidence: 99%
“…Data from SMA animal models and SMA patient motor neurons derived from induced pluripotent stem cells (iPSCs) indicate that factors intrinsic to motor neurons are important for degeneration (Park et al 2010;Corti et al 2012;Van Hoecke et al 2012). Thus, investigating cell intrinsic pathways that are differentially activated within resistant and vulnerable motor neurons could reveal mechanisms of selective neuronal degeneration and lead to therapies preventing progressive motor neuron loss (Hedlund et al 2010;Kaplan et al 2014;Comley et al 2015;Murray et al 2015;Allodi et al 2016;Nijssen et al 2017;Allodi et al 2019).…”
mentioning
confidence: 99%